(untitled) (Nordic Journal of Practical Theology, 2026)
Based on a case study of the Diakonhjemmet (Deacons’ Home), the article examines how diaconal education in Norway has adapted to and challenged governmental authorities from the 1960s until day. The development is analyzed against the backdrop of major higher education reforms initiated by the Ottosen, Hernes, and Mjøs committees in the 1960s, 1980s, and around 2000. This archive-based study shows how a male, nursing-based deacon program opened to women and received public approval as social work education. Later, Diakonhjemmet achieved college status and launched a master’s program in diaconia. In an era marked by professionalization, academization, and secularization, it was far from certain that an interdisciplinary, faith-based education would survive. Broad governmental definitions of higher education, combined with openness to faith-based institutions, and Diakonhjemmet’s strategic positioning ensured the inclusion of diaconal education in Norway’s system.